π0 and η measurement with photon conversions in ALICE in proton-proton collisions at √s=7 TeV - Koch, Kathrin (Nuclear physics. A, Nuclear and hadronic physics, 2011)
We present a measurement of the π0 transverse momentum spectrum and of the η/π0 ratio in proton-proton collisions at √s=7 TeV at the CERN LHC. In this analysis the reconstruction of π0 and η mesons has been done via photon conversions in the central tracking system of ALICE. Therefore, this method is completely independent from the electromagnetic calorimeters. It makes the π0 (η) measurement possible down to pt=0.4 (0.6) GeV/c with a very good resolution and a very small background. For 108 pp collisions the pt reach is 7 GeV/c. The results are compared to NLO pQCD calculations.